Durable Cr‐substituted (Ba, Cs)1.33(Cr, Ti)8O16 hollandite waste forms with high Cs loading. Issue 6 (7th March 2022) - Zhao, Mingyang; Birkner, Nancy; Schaeperkoetter, Joseph; Koch, Robert J.; Russell, Patrick; Misture, Scott T.; Besmann, Theodore; Amoroso, Jake; Brinkman, Kyle S.
Abstract: A series of Cr‐substituted hollandite solid solution Bax Csy Cr2x+y Ti8−2x−y O16 over a broad range of Cs content (x + y = 1.33, 0 ≤ x and y ≤ 1.33) were systematically investigated. A monoclinic‐to‐tetragonal phase transition was induced by increasing Cs content in the tunnel sites of the hollandite structure, and all members of the series show structure modulations related to the ordering of the Ba/Cs and vacancies along the tunnels. The thermodynamic stability of the Cr‐substituted hollandite samples was measured via high‐temperature oxide melt solution calorimetry, which included making the first measurements of the enthalpies of drop solution for Cs2 O and BaO in sodium molybdate solvent at 800°C. Thermodynamic stability increased with increasing Cs content for the series of Cr‐substituted hollandite, which also exhibited a greater thermodynamic stability compared to other substituted hollandite analogs including Zn, Ga, Fe, and Al variants. The leaching performance, also known as aqueous durability, demonstrated that the fractional Cs release in the Cr hollandite samples is much lower than in other hollandite systems. After 7 days of leaching at 90°C, the lowest Cs release was observed in the sample with the highest Cs content, approximately 22 wt.% Cs. The Cs release could be further suppressed, by approximately 3× if the sample was further densified and sintered. The Cs release results correlated inversely to the thermodynamic stability, suggesting that the thermodynamic stability may be used in future materials design for nuclear waste immobilization. Abstract :